2022
DOI: 10.1002/smll.202201361
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrafine Ruthenium Clusters Shell‐Embedded Hollow Carbon Spheres as Nanoreactors for Channel Microenvironment‐Modulated Furfural Tandem Hydrogenation

Abstract: Rationally modulating the catalytic microenvironment is important for targeted induction of specific molecular behaviors to fulfill complicated catalytic purposes. Herein, a metal pre‐chelating assisted assembly strategy is developed to facilely synthesize the hollow carbon spheres with ultrafine ruthenium clusters embedded in pore channels of the carbon shell (Ru@Shell‐HCSs), which can be employed as nanoreactors with preferred electronic and geometric catalytic microenvironments for the efficient tandem hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Very recently, a typical case was reported by Lu et al, in which both the electronic and geometric microenvironments of hollow nanoreactors were modulated to facilitate the tandem hydrogenation of furfural to 2-methylfuran. [94] A metal pre-chelating assisted assembly strategy was developed to synthesize the Ru@Shell-HCSs with ruthenium clusters embedded in pore channels of the shell of hollow carbon spheres. The special channel-embedded structure was shown to strengthen the electron transfer from Ru clusters to the carbon channels, thereby making the Ru clusters significantly electron-deficient, which could prompt the furfuryl alcohol hydrogenolysis, the rate-determining step of the tandem furfural hydrogenation.…”
Section: Systemic Effects Triggered By Hollow Nanoreactors On Overall...mentioning
confidence: 99%
See 2 more Smart Citations
“…Very recently, a typical case was reported by Lu et al, in which both the electronic and geometric microenvironments of hollow nanoreactors were modulated to facilitate the tandem hydrogenation of furfural to 2-methylfuran. [94] A metal pre-chelating assisted assembly strategy was developed to synthesize the Ru@Shell-HCSs with ruthenium clusters embedded in pore channels of the shell of hollow carbon spheres. The special channel-embedded structure was shown to strengthen the electron transfer from Ru clusters to the carbon channels, thereby making the Ru clusters significantly electron-deficient, which could prompt the furfuryl alcohol hydrogenolysis, the rate-determining step of the tandem furfural hydrogenation.…”
Section: Systemic Effects Triggered By Hollow Nanoreactors On Overall...mentioning
confidence: 99%
“…As mentioned earlier, a further exploitation of the systematic effects of hollow nanoreactors in terms of both electronics and geometry to promote preferred kinetic behaviors is considered as a requisite approach for achieving a better controllable catalysis with specific purposes. Very recently, a typical case was reported by Lu et al., in which both the electronic and geometric microenvironments of hollow nanoreactors were modulated to facilitate the tandem hydrogenation of furfural to 2‐methylfuran [94] . A metal pre‐chelating assisted assembly strategy was developed to synthesize the Ru@Shell‐HCSs with ruthenium clusters embedded in pore channels of the shell of hollow carbon spheres.…”
Section: Systemic Effects Triggered By Hollow Nanoreactors On Overall...mentioning
confidence: 99%
See 1 more Smart Citation
“…11 The spatial confinement reaction in nanostructures is a new engineering method to strengthen mass transfer and redox processes. 12,13 Nanoscale confinement affects the interaction between the guest molecules and the reactive surface, resulting in changes in behavior relative to the bulk phase (e.g., accumulation, distribution, and binding), and ultimately changes the kinetics of various redox reactions. 14,15 Previous studies have shown that the confined microenvironment changes the energy and kinetics of the catalytic reaction by imposing specific orientation and conformation on the reactant molecules.…”
Section: Introductionmentioning
confidence: 99%
“…These platform molecules that are obtained from cellulose, hemicellulose or lignin have been reported to be efficiently converted into a wide range of value-added chemicals and liquid fuels through various upgrading strategies. [42][43][44][45][46] Biomass-derived ketones are an important class of platform molecules, which can be classified as cyclic ketones and linear ketones. Among these ketones, the linear diketones have received extensive research attention in recent years due to their inherent high value and huge application potential.…”
Section: Introductionmentioning
confidence: 99%